Kasus Perdagangan Manusia di Indonesia Ditinjau dari Undang-Undang Nomor 21 Tahun 2007 Tentang Tindak Pidana Perdagangan Orang - Khosy Zufar Annaafi (Universitas Muhammadiyah Purwokerto, 2019)
Human trafficking, especially children, has become a phenomenon that is unceasingly prevented or eradicated in this world. Although there are many regulations to protect children, in fact, children always tend to be used as objects for certain individuals to be traded. Then “Undang-Undang Nomor 21 Tahun 2017 Tentang Tindak Pidana Perdagangan Orang” in Persons can be a protector for victims of human trafficking. Then the legislation is expected to be a deterrent effect for perpetrators. This article is expected to provide education to the public about trafficking in persons and to be a correction by the government regarding trafficking in persons.Keywords: Child Protection, Human Trafficking, education, and correction